Impact of ICT on Education: Challenges and Perspectives - Hernandez, Ronald M. (2017)
This paper sets out the main challenges and provides an overview of the future of ICTs and their connection with education. It begins with a description of the so-called knowledge-based society and how its evolution, an offspring of technology, has encompassed different areas, paving the way for innovation in education and prompting generation of new knowledge. It also outlines the importance of each educational agent (teacher-student) and their role in transforming the teaching-learning process.